“Modelación espacial de idoneidad y adaptabilidad de áreas de conservación del suelo agrícola ante cambios climáticos en el cantón Valencia, provincia de Los Ríos” - Espín Acosta, Jessica Jazmín (2022)
Climate changes represent a latent threat that has an increasing influence on agricultural plantations, which causes vulnerability of certain geographical areas with a low level of resilience. Therefore, soil conservation is one of the main challenges facing agricultural activity today, for which it is necessary to implement adaptation and mitigation strategies to climate change; For this reason, the main objective of this research is to identify the optimal areas for the agricultural production of the main crops of the Valencia canton (Cacao, African Palm and Banana) through spatial modeling of suitability and adaptability of areas. which a methodology made up of the types of descriptive, exploratory and diagnostic research was used, where the following official sources were determined with primary sources of information: SIGTIERRAS, MAATE, SNI and GEO PORTAL of IGM, where it was downloaded vector layer files or shp databases, tables and official documents referring to the object of study. In the same way, cartographic parameters were used such as: scale, reference system, cartographic projection and cartographic zone to measure two analysis edges that are: the soil change that the crops of the city of Valencia and its respective agricultural zoning, all through the use of the Arcgis Los software. The results of th